Implementation of the Procurement Function and its Influence on Project Performance - Al Khaja, Esam (2012)
Project management has been heavily affected by procurement functions and the performance of projects is fundamentally associated with them. The research for this dissertation analyses the implications of inadequate implementation of the procurement functions and particularly their role in ineffective project performance. Three problem cases related to various projects in NPCC, an oil and gas construction company are considered. This organisation has suffered from different and improper implementation of procurement functions which have affected project outcomes. These cases were analyzed based on five main project concepts: Project Scope, Project Schedule, Project Stakeholder, Project Progress and Procurement Issues. Interviews were conducted with relevant stakeholders, project managers and users participated in the problem cases to investigate the procurement issues that were contributing to the problems. The results showed that issues like clear interpretation of scope of work to the invited bidders, qualification based contractor selection, maintaining proper communication channels, implementation of non-traditional procurement methods and contractor's previous performance prior to the award can all contribute to better project performance. This study concludes that the role of stakeholder has to be more effective in enhancing the procurement functions and recommends further future research for academics and practitioners. Moreover, recommendations are presented for different stakeholders in NPCC, Client Organizations and the UAE Government.